The Implementation of Jigsaw Learning Model in Prevention of Bullying in Fourth Grade Students - Aditiyo Wibowo; Ratsimandresy Faly William; Penina Kacimaiwai (Elementary Education Journal, 2022)
Background: The purpose of this study was to reveal the negative impact of bullying and also appropriate strategies to prevent bullying in an elementary school. Method: This study was a  descriptive qualitative. The study was conducted at 31 Public Elementary School (31PES), OKU, Battu Winangun Village, Lubuk Raja District, Ogan Komering Ulu Regency, South Sumatra Province, Indonesia. Result: The results showed that the majority of students were active from both affective and cognitive sides in learning with the Jigsaw learning model in preventing bullying. Therefore, it can be understood that in the learning process that is managed by the teacher to students, the teacher plays an important or crucial role. So that a conducive atmosphere needs to be formed by the teacher so that a good relationship with students will be formed. So they can carry out various learning activities effectively. Implications: Jigsaw learning model was effective in bullying prevention. Students can be more active in understanding learning in groups and individually. Novelty: This study revealed the effectiveness of learning by using the Jigsaw learning model as an effort to prevent bullying in elementary school.